Moisture and nitrogen stress induces severity of wilt-nematode complex of lentil grown in rice fallow in an Inceptisol - NIRMAL DE, SUMIT KUMAR PANDEY; RAKESH KUMAR SINGH, RAJ MUKHOPADHYAY*, VICTOR PHANI (Indian Phytopathology, 2017)
Lentil (Lens culinaris) is a leading high protein pulse grown by the farmers as a rainfed rabi crop in lowland rice fallows in Indo Gangetic Plains (IGP) of India. Disease complex due to Fusarium oxysporum and Meloidogyne incognita possess a great threat to yield of lentil when grown as fallow crop after rice with residual soil moisture and nitrogen in dryland condition. This paper discusses the role of soil moisture and availability of soil NO3-N to the plants on wilt nematode disease complex under a long term rice-lentil cropping system. In our long term experimental conditions which prevailed under dry condition, low level of soil moisture and low availability of soil NO3-N to plants illustrated increased in fungus nematode wilt complex severity which can be mitigated by use of farm yard manure as full source of nitrogen in rice. This leads to the enhancement of the available soil moisture and nitrogen for residual crops like lentil and also reduced wilt nematode complex.